ANALISIS PENDAPATAN USAHA MINUMAN SARI TEBU DI KECAMATAN TAMPAN KOTA PEKANBARU - Renta Minar Marlinang Pasaribu; Ermi Tety; Jumatri Yusri (Indonesian Journal of Agricultural Economics, 2018)
The purposes of this research were to know the cost, production, income, and break event pointvalue of sugarcane juice buisness in Tampan district Pekanbaru City. Sampling method usedwas purposive sampling method based on citeria of business period, type of drink, type of work,and tools used. Data collection was conducted by observation, interview and documentation.Data analysis techniques used to calculate the income and efficiency level of the juice businessusing R/C Ratio analysis. Research results obtained total cost, income, profit and break eventpoint business of sugarcane juice business. Total production cost of sugarcane juice business isIDR 43,382,718 per month with average production cost of IDR 2,160,726 per month. Totalbusiness income is IDR 22,369,349 per month with average income of each respondent of IDR1,118,467 per month. R/C Ratio Value of sugarcane juice business is 1.51 therefore the businessis feasible to continue. The value of break event points of business in the number of cups is 341while the value of break event points of business in IDR is 1,704,617.